Acoustic Coordinated Reset Neuromodulation: A Systematic Review of a Novel Therapy for Tinnitus - Wegger, Marie; Ovesen, Therese; Larsen, Dalia Gustaityte (Frontiers in Neurology, 2017)
Abstract Background: There are growing technological advances in the development of sound-based methods for the treatment of tinnitus. Most of these methods intend to affect the speculated underlying neurological causes of tinnitus. Acoustic Coordinated Reset (CR) neuromodulation is one of them. A novel method that as of yet seems inadequately reviewed. Purpose: To evaluate the current evidence on acoustic CR neuromodulation as a method for the treatment of tinnitus, and to assess whether the method can be implemented in daily clinical practice. Methods: A systematic literature search was performed in 13 databases in the period from the February 1st 2015 to May 1st 2016. Studies regarding acoustic CR neuromodulation as a treatment method for tinnitus were included in the present review. Results: A total of eight studies were eligible for being reviewed comprising a total of 329 patients. Overall, the evidence level of the published literature was low. The main findings in the included studies were that acoustic CR neuromodulation was safe and well tolerated and most patients reported reduction of tinnitus symptoms. The neurophysiological basis of the method was claimed to be desynchronization, anti-kindling and change of abnormal frequency couplings in a widespread tinnitus network comprising both auditory and non/auditory brain areas based on EEG analyses. Conclusion: The available evidence is insufficient for clinical implementation of acoustic CR neuromodulation. The limited level of evidence suggests that acoustic CR neuromodulation may have positive effects on tinnitus symptoms. Preliminary electroencephalographic data are compatible with the claim that tinnitus reduction after CR treatment is mediated by a desynchronizing effect. However, a proof for this claim is still lacking.